Post-fire stress-strain response of structural ferritic stainless steels. (September 2022) - Xie, Li-An; Wang, Xing-Qiang; Han, Zhi-Jiang; Yu, Xin; Alim, Mohammad A.; Manninen, Timo; Tao, Zhong
Abstract: In this study, the effects of heating temperature and heat soak time on the post-fire stress-strain behaviour of three ferritic stainless steel grades (i.e., EN 1.4003, 1.4016, 1.4509) are experimentally investigated. The test results revealed that the three grades behaved very differently after exposure to elevated temperatures because of microstructure changes during heating and cooling down to room temperature. The heating temperature affected not only the residual strength and deformation capacity but also the shape of the stress-strain curve. A prolonged heat soak had no noticeable effect on the steel grade 1.4509 but increased strength loss of grades 1.4003 and 1.4016. Two stress-strain models, i.e., one exhibiting continuous yielding (without yield plateau) and the other with yield plateau, were proposed to use jointly to capture the post-fire stress-strain response of the three ferritic grades. Graphical abstract: Unlabelled Image Highlights: As-received ferritic alloys with a ferrite matrix exhibit continuous yielding. Heating can change the shape of stress-strain curves of ferritic alloys. Loss in yield stress is up to 20% after exposure to 300–1000 °C. Soak time can affect the residual strength of 1.4003 and 1.4016. Two stress-strain models can be used jointly to predict the post-fire response.